Motor development of children exposed to the zika virus: systematic reviews - Maysa Ferreira Martins Ribeiro; Karla Beatriz Presto de Queiróz; Cejane Oliveira Martins Prudente (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to describe the motor development, in the first two years of life, of children with evidence of congenital Zika virus syndrome (CZS) at birth and of children exposed to the Zika virus (ZIKV) during pregnancy, but without evidence of CZS. Methods: systematic review, according to the recommendations of the Preferred Reporting Items for Systematic Reviews (PRISMA). The search took place in the VHL/LILACS interface and BIREME/ PubMed interface databases until March 2020. Two researchers analyzed the quality of the studies using the Johanna Briggs Institute methodology. Results: 21 articles were selected. Children with CZS have severe impairment of motor functions and a high prevalence of spastic cerebral palsy. At two years of life, most reached only early levels of motor development; with impaired vision, hearing, language, cognition, behavior, and social interaction. On the other hand, children exposed to ZIKV, but without evidence of CZS, are at lower risk, about 20% have late manifestations of delay and/or neurodevelopmental disorder. Variables associated with greater motor impairment are early maternal infection, preterm birth, lower head circumference, abnormal imaging, use of anticonvulsant, increasing age, arthrogryposis, epilepsy, deficits in vision, language, cognition, and lower income. Conclusion: Most children with CZS show severe motor impairment; a small part of those exposed to ZIKV, without evidence of the syndrome at birth, have alteration in neurodevelopment. Those children should be followed in the long-term, since some manifestations may occur belatedly.